Government support and profitability effects – Vietnamese offshore fisheries. (November 2015) - Duy, Nguyen Ngoc; Flaaten, Ola; Long, Le Kim
Abstract: Bioeconomic theory and empirical evidence have demonstrated that open-access fisheries tend to break even and also that intra-marginal rent may be generated in heterogeneous fleets. Theoretically, input and output subsidies are expected to increase profit in the short term, but not in the long term. Vietnamese government subsidies of offshore fishing vessels are investigated and quantified, and their profitability effects are examined, through representative surveys of costs and earnings data. The subsidy schemes had positive effects on vessel profitability, with the quasi-lump sum fuel cost support having the greatest effect. The largest vessels received relatively more support than the smaller ones and earned most of the super-profit as well as the intra-marginal rent generated. However, higher subsidies for larger vessels did not help all of them achieve higher economic performance. The subsidisation programmes may come from infant industry arguments, the strategic rent-shifting incentives of neighbouring countries, social and geopolitical objectives, and because of South China Sea border security reasons. Highlights: Government support and profitability effects was investigated and quantified. Subsidies increased the profitability in the short term, but not in the long term. Larger vessels received relatively more support than small ones and earned most rent. Higher subsidies did not help all larger vessels achieve higher economic performance. Subsidies to prevent collapse of fishing communities are at its best a short-term remedy.